PERENCANAAN PAKET WISATA TIRTA DI KABUPATEN BULELENG - Swandewi, Luh Putu; Sudana, I Putu; Indrawati, Yayu (Jurnal IPTA (Industri Perjalanan Wisata), 2014)
Buleleng has variety attraction for tourism industry, such as natural and cultural potencies of tourism destination and most of it, is about marine tourism but there are none of them providing water tour packages. The purpose of this field study is to identify the marine tourism potency in Buleleng Regency and plan a marine package tour using distribution channel model of the marine package tour which have to planning for new brand on package tour in Bali, especially about the promotion for alternative tourism of the marine tour package must be increased the tourist arrivals to Buleleng Regency. The final result of this study indicated from the observations which the potencies of marine tourism in Buleleng has not been developed and get attention, especially from the local government with required the promotion for marine tourism attraction in Buleleng Regency. In addition of the marine tourism package can be used for the local society and make satisfied of the package tour for tourist who arriving for holiday in Buleleng Regency.
Keywords: Marine Tourism, Potency, Tour Package